The influence of compensation interdependence on risk-taking: the role of mutual monitoring - Felix Bolduan; Ivo Schedlinsky; Friedrich Sommer (Journal of Business Economics, 2021)
This study investigates if and how the influence of compensation interdependence on risk-taking depends on mutual monitoring of risky investment decisions. We argue that individuals under compensation interdependence have a behavioral incentive for higher risk-taking if mutual monitoring is present. Impression management is hypothesized to be the driving force behind this effect, with the visibility of actions to the peers through mutual monitoring as an important prerequisite. The results of a laboratory experiment support our predictions. Additional analyses reveal that impression management drives our results because participants incorporate their peers' preferences in their decision process. This reasoning is further substantiated as individuals increase their risk-taking if they took less risk than their peers in previous experimental rounds and thus adjust to their respective peer group. Our findings inform firms about the effect of compensation interdependence in working environments with differing opportunities for mutual monitoring.
Keywords: M12; M41; M52; 650; Risk-taking; Compensation interdependence; Mutual monitoring; Impression management; Social reasoning